Epidemiology of meningococcal disease in north america. - Pollard, A; Scheifele, D; Rosenstein, N (2001)
Invasive disease caused by Neisseria meningitidis is one of the leading infectious causes of death in childhood in North America (1), but its prevention has not received the same priority on the health agenda as in Europe, Australia, and New Zealand. There are several likely explanations, but the principal one is that disease incidence appears to be lower in both Canada (2) and the United States (3) than in some of these other countries (4,5). Here, we describe recent epidemiological data concerning meningococcal infection in Canada and the United States and comment on the possible future introduction of vaccination to prevent meningococcal disease across the continent.